2015
DOI: 10.1111/twec.12333
|View full text |Cite
|
Sign up to set email alerts
|

Services Productivity, Trade Policy and Manufacturing Exports

Abstract: This paper analyses the linkage between services and manufacturing productivity performance, using firm‐level data for over 100 developing countries. We find strong evidence for such a linkage, although the effect is small: at the average rate of services input intensity, a 10 per cent improvement in services productivity is associated with an increase in manufacturing productivity of 0.3 per cent. Services trade restrictiveness indices are found to be a statistically significant determinant of manufactured ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 43 publications
(65 reference statements)
1
69
0
8
Order By: Relevance
“…The role of services as a path to growth that complements the primary and secondary sector, as opposed to a sole focus on manufacturing, has been highlighted in various recent studies, a number of which link the positive effect of services on economic transformation to, at least in part, the increasing tradability and contestability of services markets (Jensen and Kletzer, 2005;Jones and Kierzkowski, 1988;Riddle, 1986;Eichengreen and Gupta, 2013;Schettkat and Yocarini, 2006;Cali et al, 2008). Globalization in various services sectors provides greater opportunities to specialize, exploit comparative advantage, and export, but increased contestability and improved service sector performance also help improve productivity in non-services sectors of the economy (Hoekman and Shepherd, 2017;Nordås and Kim, 2013). Ghani and O'Connell (2014) argue that services can drive growth and create good jobs in countries at different levels of development.…”
Section: Services In Domestic Economies and Its Importance For Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of services as a path to growth that complements the primary and secondary sector, as opposed to a sole focus on manufacturing, has been highlighted in various recent studies, a number of which link the positive effect of services on economic transformation to, at least in part, the increasing tradability and contestability of services markets (Jensen and Kletzer, 2005;Jones and Kierzkowski, 1988;Riddle, 1986;Eichengreen and Gupta, 2013;Schettkat and Yocarini, 2006;Cali et al, 2008). Globalization in various services sectors provides greater opportunities to specialize, exploit comparative advantage, and export, but increased contestability and improved service sector performance also help improve productivity in non-services sectors of the economy (Hoekman and Shepherd, 2017;Nordås and Kim, 2013). Ghani and O'Connell (2014) argue that services can drive growth and create good jobs in countries at different levels of development.…”
Section: Services In Domestic Economies and Its Importance For Growthmentioning
confidence: 99%
“…Services trade policies also have implications for international merchandise trade. Achieving a reduction in trade costs for goods largely hinges on improving the performance of the services used by goods-producing enterprises, reducing their cost and increasing their diversity and quality (Hoekman and Shepherd, 2017). A body of country-specific research has firmly established that openness in services trade positively affects the productivity of manufacturing industries (Arnold et al, 2011;Arnold et al, 2015;Arnold et al, 2008;Duggan et al, 2013).…”
Section: Restrictions On Services Trade Negatively Impact Manufacturimentioning
confidence: 99%
See 1 more Smart Citation
“…Such bundling of trade in goods and services by firms provides another mechanism through which services liberalization can boost manufacturing exports. Other studies have shown that services trade liberalization (or restrictiveness) affects the performance of the manufacturing sector in terms of exports (Hoekman & Shepherd, ; Liu, Mattoo, Wang, & Wei, ; Nordås & Rouzet, ; Van der Marel, ) and productivity (Arnold, Javorcik, Lipscomb, & Mattoo, ; Arnold, Javorcik, & Mattoo, ; Beverelli, Fiorini, & Hoekman, ). However, most of the empirical studies on the impact of services liberalization on the goods sector use country‐level measures of services restrictiveness while this paper links preferential liberalization of services to manufacturing GVCs.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we build on this literature to assess the effects of services-related policies on manufacturing employment for a panel of transition economies. Rather than focus on the impact 1 Firm-level analyses of productivity effects include Arnold et al (2008Arnold et al ( , 2011; Fernandes and Paunov (2011);Forlani (2012); Duggan et al (2013); Bas (2014); Hoekman and Shepherd (2015) and Arnold et al (2016). Studies using sector-level data include Barone and Cingano (2011); Bourlès et al (2013) and Beverelli et al (2015).…”
Section: Introductionmentioning
confidence: 99%